2009
DOI: 10.1007/s10689-009-9238-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of families with Lynch syndrome complicated by advanced serrated neoplasia: the importance of pathology review and pedigree analysis

Abstract: The identification of Lynch syndrome has been greatly assisted by the advent of tumour immunohistochemistry (IHC) for mismatch repair (MMR) proteins, and by the recognition of the role of acquired somatic BRAF mutation in sporadic MMR-deficient colorectal cancer (CRC). However, somatic BRAF mutation may also be present in the tumours in families with a predisposition to develop serrated polyps in the colorectum. In a subgroup of affected members in these families, CRCs emerge which demonstrate clear evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…A single false-negative was identified adding to the increasing number of LS tumors harboring a BRAF mutation. 22 In contrast, its specificity is low. Two factors may account for this observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A single false-negative was identified adding to the increasing number of LS tumors harboring a BRAF mutation. 22 In contrast, its specificity is low. Two factors may account for this observation.…”
Section: Discussionmentioning
confidence: 99%
“…37 This case shares a BRAF mutation and promoter hypermethylation, the expected scenario for a non-LS tumor. 10,11,14,15 Walsh et al 22 reported the presence of a BRAF mutation in a member of a LS family that, also showed predisposition to develop colorectal serrated polyps. Interestingly, some evidence suggests that non-LS MSI-H cases may originate from sessile serrated adenoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lack of BRAF mutation is highly sensitive for a syndromic tumor, rare BRAF mutations have been described in patients with Lynch syndrome. 14,20 As well, BRAF V600E mutations have been described in Lynch syndrome probands with monoallelic PMS2 mutations. 21 Testing for BRAF mutations can be performed by Sanger sequencing and pyrosequencing, allele-specific reverse transcription-PCR, mass spectrometry-based sequencing, high-resolution melting curve analysis, and next-generation sequencing methods using microfluidics technology, among others.…”
Section: Microsatellite Instability and Lynch Syndromementioning
confidence: 99%
“…However, four studies have identified 16! the BRAF V600E mutation and a germline MMR gene mutation in MLH1, MSH2 and PMS2 32,82,260,261 . Therefore the presence of a BRAF V600E mutation in a CRC, while a strong negative predictor of carrying a MMR mutation should not be assumed to exclude positive mutation status for any of the four MMR genes, particularly in the context of a family history suggestive of LS.…”
Section: Mlh1 Promoter Methylation and Braf V600ementioning
confidence: 99%